Obstacles to the Spread of E-Learning in the Arab Countries - Harith Abood Abbas (Journal of Education and Learning (EduLearn), 2016)
This study aimed at investigating the obstacles hindering the spread of e-learning in the Arab countries. 400 of Arab universities teaching staff members were randomly selected to give their opinion on 48 statements of a questionnaire. The results showed that the main obstacles are: the need for face-to-face communication between teachers and students, lack of English and computer skills, as well as the lack of technological infrastructure and a legal framework that may let the adoption of this kind of education be possible.